Monotonic and fracture behaviours of bolted connections with distinct bolt preloads and surface treatments - Vtor M.G. Gomes; Mariana Rodrigues; Jos A.F.O. Correia; Miguel A.V. Figueiredo; Ablio M.P. de Jesus; Antnio A. Fernandes (Fracture and Structural Integrity)
This paper presents a research about the monotonic and failure behaviours of bolted joints made of thin plates of S350GD and S355MC steels grades applied for rack structures. A full factorial matrix of static monotonic tests was performed considering two joints configurations, two material thicknesses, three surface coatings and two preload levels. Slip tests were also performed according to the EN 1090-2 standard to evaluate joint slip factors for the three material surface conditions. Numerical simulations of static tests were also performed using J2 plasticity and compared with experimental data. From experimental results, it is verified that increasing thickness and preload results an increasing of failure loads and sliding loads, respectively. Slip tests revealed the lowest slip factors for the painted specimens, followed by uncoated specimens and the higher slip factor was verified for zinc-coated specimens. Regarding failure modes, it verified that the S355MC specimens with single connection fractured by shear, while the S350GD specimens fractured from splitting and shear. In addition, for specimens with multiple connections for both materials, the failure occurred in net cross-section. The FE results reproduced conveniently the ultimate loads as well as the failure modes, including the clamping and friction effects.